Theoretical Basis of Determining the Translation and Rotation of Steering Wheel Stub Axle - STRUSKI, Józef; WACH, Krzysztof (Engineering Transactions, 2012)
In the paper a theoretical basis of determination of the steering wheel stub axle position and orientation in the suspension movements space, realized by the suspension mechanism are presented. The designed instrument allows measurement of quantities that are needed to com- pute the translation and orientation of the stub axleand to draw the kinematic characteristics of the suspension.